Nonlinear Displacement of the Electrothermal V-Shaped Actuator - Truong Duc Phuc; Phuc Hong Pham; Kien Trung Hoang; Bui Ngoc-Tam (Shock and Vibration)
This article proposes a formula for calculating the nonlinear displacement of the electrothermal V-shaped actuator aims to determine more accurately its displacement. The nonlinear displacement model is established based on the axial deformation of V-beams with two fixed ends. Hence, the theoretical displacements of a particular V-shaped actuator (i.e. dimension as beam length of 750 μm; beam width of 6 μm; beam thickness of 30 μm; inclined angle of 2°) are compared with the simulation and experimental results. The evaluation shows that our calculation error compared with the simulation and experiment is less than 5% and 12.4%, respectively. This confirmed the advantages of the proposed formula according to the nonlinear displacement model. This work provides a theoretical model for predicting more precisely the displacement of a V-shaped actuator. The advantage of this model is that it will significantly reduce the time in the design and trial manufacturing process.